2011
DOI: 10.1002/btpr.662
|View full text |Cite
|
Sign up to set email alerts
|

In vivo post‐translational modifications of recombinant mussel adhesive protein in insect cells

Abstract: Mussel adhesive proteins (MAPs) have been suggested as promising bioadhesives for diverse application fields, including medical uses. Previously, we successfully constructed and produced a new type of functional recombinant MAP, fp-151, in a prokaryotic Escherichia coli expression system. Even though the E. coli-derived MAP showed several excellent features, such as high production yield and efficient purification, in vitro enzymatic modification is required to convert tyrosine residues to l-3,4-dihydroxypheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…These results demonstrated that tyrosines at position 5 in the decapeptide unit of the fp-1 region in the co fp-151 were in vivo modified into Dopaquinone through co-expression of tyrosinase, although the modification of tyrosine residues was more frequently detected at position 9 than position 5 in the natural fp-1 [25]. Previously, the tyrosine modification at position 5 was observed in synthetic fp-1 decapeptide conversion using mushroom tyrosinase [9] and was also observed with in vivo modification of fp-151 in insect Sf9 cells [26]. Thus, the altered preference of hydroxylation position might be due to the different modification enzymes and/or the different structural features of fp-151.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that tyrosines at position 5 in the decapeptide unit of the fp-1 region in the co fp-151 were in vivo modified into Dopaquinone through co-expression of tyrosinase, although the modification of tyrosine residues was more frequently detected at position 9 than position 5 in the natural fp-1 [25]. Previously, the tyrosine modification at position 5 was observed in synthetic fp-1 decapeptide conversion using mushroom tyrosinase [9] and was also observed with in vivo modification of fp-151 in insect Sf9 cells [26]. Thus, the altered preference of hydroxylation position might be due to the different modification enzymes and/or the different structural features of fp-151.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many native protein-based materials incorporate repetitive sequences that include multiple sites of post-translational modification that are critical for appropriate biological function, e.g., trans -hydroxyproline in collagens, [5253] or DOPA residues in mussel adhesive proteins. [54] The multi-site suppression techniques represents an attractive approach to the synthesis of these functional materials, which are challenging to obtain from in vitro chemical or in vivo enzymatic modification of the native protein sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other mussels species, A. ater contains 15-20 times more adhesive polyphenolic proteins than any other mussels [72]. Protocols aimed at optimizing large scale production of these biological adhesive for their industrial usage have recently been developed and may accelerate the use of such bioinspired proteins in various biomedical and tissue engineering fields [73,74].…”
Section: Economical Perspectivementioning
confidence: 99%